Effects of erythromycin and roxithromycin on river periphyton: Structure, functions and metabolic pathways. (March 2023) - Yan, Shiwei; Ding, Ning; Yao, Xiunan; Song, Jinxi; He, Wei; Rehman, Fozia; Guo, Jiahua
Abstract: Macrolides have been frequently detected in the surface waters worldwide, posing a threat to the aquatic microbes. Several studies have evaluated the ecotoxicological effects of macrolides on single algal and bacterial strains. However, without considering the species interaction in the aquatic microbial community, these results cannot be extrapolated to the field. Thus, the present study aimed to evaluate the effects of two macrolides (erythromycin and roxithromycin) on the structure, photosynthetic process, carbon utilization capacity, and the antibiotic metabolic pathways in river periphyton. The colonized periphyton was exposed to the graded concentration (0 μg/L (control), 0.5 μg/L (low), 5 μg/L (medium), 50 μg/L (high)) of ERY and ROX, respectively, for 7 days. Herein, high levels of ERY and ROX altered the community composition by reducing the relative abundance of Chlorophyta in the eukaryotic community. Also, the Shannon and Simpson diversity indexes of prokaryotes were reduced, although similar effects were seldomly detected in the low and medium groups. In contrast to the unchanged carbon utilization capacity, the PSII reaction center involved in the periphytic photosynthesis was significantly inhibited by macrolides at high levels. In addition, both antibiotics had been degraded by periphyton, with the removal rate of 51.63–66.87% and 41.85–48.27% for ERY and ROX, respectively, wherein the side chain and ring cleavage were the main degradation pathways. Overall, this study provides an insight into the structural and functional toxicity and degradation processes of macrolides in river periphyton.– Graphical abstract: Image 1 Highlights: Photosystem II in periphyton was inhibited by erythromycin and roxithromycin. Exposure to both antibiotics did not alter 31 carbon sources utilization capacity. Shannon & Simpson indexes were decreased for prokaryotes but increased for eukaryotes. The side chain and ring cleavage were the main degradation pathways for macrolides.